Ecosystem Services, Global Diversity, and Rate of Stonefly Species Descriptions (Insecta: Plecoptera) - R. Edward DeWalt (Insects, 2019)
Stoneflies (Insecta: Plecoptera) provide ecosystem services as indicators of water quality, as food for predators, as mediators of energy flow and nutrient cycling, and through cultural services related to recreation and artistic creativity. The Plecoptera Species File (PSF) aggregates stonefly nomenclature, distribution, and literature to help society and scientists understand the value of services stoneflies provide. Using PSF data, we examined global and regional diversity, compared species description rates, and predicted future species description numbers through the year 2100. Through 2018, extant species totaled 3718 with Temperate Asia having the greatest regional diversity at 1178 species. The Perlidae was the most species-rich of the 16 families at 1120 species. The recent global rate of species description was 43.6 species/yr, with Temperate Asia having the highest regional rate at 13.7 species/yr, followed by China and South America adding approximately 9.0 species/yr. We predicted that 1140 ± 130 new species would be described globally by 2050, and 2130 ± 330 by the year 2100, most of the increase occurring in China and South America. We discuss the possibility of reaching these predicted values.